2023
DOI: 10.3390/v15051150
|View full text |Cite
|
Sign up to set email alerts
|

Novel Rodent Arterivirus Detected in the Brazilian Amazon

Abstract: As part of a continuous effort to investigate the viral communities associated with wild mammals at the human–animal interface in an Amazonian metropolitan region, this study describes the detection of a novel rodent-borne arterivirus. A sample containing pooled organs of Oecomys paricola was submitted to RNA sequencing, and four sequences taxonomically assigned as related to the Arteriviridae family were recovered, corresponding to an almost complete genome of nearly 13 kb summed. In the phylogenetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…These hypotheses are in accordance with the first reported event describing PDD signs in birds imported from Bolivia [ 4 ]. Interestingly, other studies have also identified basal clades or branches from divergent viruses detected in Brazil [ 53 , 54 ], raising concerns when unexplored ecosystems that may contain these and other viral species are contacted, altered, or destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…These hypotheses are in accordance with the first reported event describing PDD signs in birds imported from Bolivia [ 4 ]. Interestingly, other studies have also identified basal clades or branches from divergent viruses detected in Brazil [ 53 , 54 ], raising concerns when unexplored ecosystems that may contain these and other viral species are contacted, altered, or destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the emergence of new virus species and/or isolates infecting wild animals from the interface between forest/rural/metropolitan areas and animals from growing farms were the most prevalent issues in this SI. New arteriviruses, hepinaviruses, coronaviruses, and astroviruses were identified in rodent, vole, and gosling species, respectively [ 1 , 2 , 3 , 4 ]. Also, new isolates of high pathogenic H5N1 influenza virus, epizootic hemorrhagic disease virus strain (EHDV), and Lumpy skin disease virus (LSDV) were reported in wild birds and poultry, cattle, and yaks [ 5 , 6 , 7 ].…”
mentioning
confidence: 99%
“…Human–animal interface in the Amazonian metropolitan area represents a constant opportunity for the emergence of new viruses. In an effort to identify viral communities in wild animals from this region, Da Paz and collaborators [ 1 ] conducted expeditions between 2014 and 2015, in the Belém metropolitan mesoregion of Pará State, Brazil, and collected serum and tissues from 39 mammals, comprising 18 marsupials, 12 rodents, and 9 chiropterans. Metagenomic analyses from pooled tissue samples obtained from rodents, morphologically identified as Oecomys sp., unveiled a new arterivirus, classified in the Variarterivirinae clade.…”
mentioning
confidence: 99%